Containment of Projective Identification as a Means of Ego Development: Theological Considerations - Souder, Janet K. (Journal of psychology and theology, 1986)
One assumption in the work of integrating psychological theories with theological theories is that both may benefit from the shared truth underlying the systems. In psychoanalysis the development of the ideas of projective identification and the containing function of the object projectively identified, has provided a means for conceptualizing early ego development In particular the theories of Klein (1946/1975), and the expansion and clarification of them provided by Grotstein (1981) provides a model of the importance of containment both in the mother-infant and the analyst-patient dyads. This article will expand the model of containment from the theological perspective of the person and atoning work of Jesus Christ